Deciphering cis/trans RNA regulatory interactions in vivo - Steinkraus, BR (2016)
Post-transcriptional regulation of the genetic programme is achieved through the sophisticated interplay between cis regulatory elements and trans interacting factors. Deciphering these interactions, especially those between microRNAs (miRNAs) and destabilising miRNA response elements (MREs), requires technologies that permit their unbiased interrogation under native, physiological conditions. Here I describe the development of miR-TRACE, a novel and versatile platform for miRNA-target identification that analyses in vivo miRNA-MRE binding. Following iterative optimisation I demonstrate the reliability of this technology in identifying bona fide miRNA targets on a candidate scale. Subsequently, I implement several experimental and computational innovations to develop miRTRACEseq, a multiplex platform enabling unbiased high-throughput analysis of miRNA-MRE interactions across the transcriptome. As a proof of concept, I applied this technology to a highly conserved candidate miRNA in S2R+ cells (miR-184) and implemented a logistic regression model to map all miR-184 MREs. This analysis confirmed known miR-184 MREs but also discovered novel targets. In parallel, during my thesis I have applied the core principles underlying miRTRACE to study the translational quiescence of bicoid (bcd) mRNA during Drosophila oogenesis. Several lines of evidence, foremost bcd’s association to mRNA processing bodies (P-bodies), suggest the possibility of a miRNA-mediated mechanism underlying bcd silencing. To explore this scenario I have developed a multipronged experimental approach employing miR-TRACE, unbiased small RNA interactome capture, and computational analysis. Together, these analyses uncovered several miRNAs specifically associated with bcd RNA in ovary tissues, of which the two most notable candidates were miR-184 and miR-989. Interestingly, the levels of these miRNAs are significantly reduced in a bcd pulldown from embryos, a finding consistent with relief of bcd silencing in this tissue. This study provides the first evidence for a potential role of miRNAs in regulating the translation of bcd RNA. This opens up a completely new line of investigation in the quest for elucidating what remains one of the most enigmatic accounts of gene expression regulation during the oocyte-to-embryo developmental transition.